What works in conservation 2015 - Sutherland, William J.; Dicks, Lynn V.; Ockendon, Nancy; Smith, Rebecca K. (What works in conservation series, 2015)
"Is planting grass margins around fields beneficial for wildlife? Which management interventions increase bee numbers in farmland? Does helping migrating toads across roads increase populations? How do you reduce predation on bird populations? What Works in Conservation has been created to provide practitioners with answers to these and many other questions about practical conservation. This book provides an assessment of the effectiveness of 648 conservation interventions based on summarized scientific evidence relevant to the practical global conservation of amphibians, reducing the risk of predation for birds, conservation of European farmland biodiversity and some aspects of enhancing natural pest control and soil fertility. It contains key results from the summarized evidence for each conservation intervention and an assessment of the effectiveness of each by international expert panels. The volume is published in partnership with the Conservation Evidence project and is fully linked to the project's website where more detailed evidence and references can be freely accessed."--Publisher's website